An Epworth Sleep Score ≥11 is associated with emergency operative birth and poor neonatal composite outcome at term. (29th May 2019) - Robertson, Nicole; Flatley, Christopher; Kumar, Sailesh
Abstract : Background: During pregnancy, the Epworth Sleepiness Scale can be used as a surrogate marker for maternal sleep‐disordered breathing, a condition that is becoming increasingly prevalent in obstetric populations and is associated with a multitude of pregnancy complications. Aims: The aim of this observational study was to investigate the relationship between the Epworth Sleepiness Scale score and indication and mode of delivery during pregnancy. Materials and Methods: The Epworth Sleepiness Scale was completed by 178 women at Mater Mothers' Hospital, Brisbane, Australia. Results: Women with a score ≥11 were less likely to achieve a spontaneous vaginal delivery (aOR 0.43, 95% CI 0.21–0.88, P = 0.02), and were more likely to have an instrumental (aOR 2.81, 95% CI 1.30–6.08, P = 0.01) or any operative birth (instrumental and caesarean section aOR 2.32, 95% CI 1.14–4.71, P = 0.02). These women were also more likely to have an operative birth for intrapartum fetal compromise (aOR 2.62, 95% CI 1.21–5.69, P = 0.015), as well as an infant with poor neonatal outcomes (aOR 2.77, 95% CI 1.09–7.03, P = 0.03). Conclusions: These results show that symptoms of sleep‐disordered breathing are associated with emergency operative birth, particularly when the indication for operative birth was intrapartum fetal compromise.